Case Report: A hybrid approach of selective adrenal artery and venous embolization for the treatment of unilateral aldosterone-producing adenoma - Yang, Changqiang; Liu, Sen; Wang, Peijian (Frontiers in Cardiovascular Medicine, 2025)
Selective adrenal artery embolization (SAAE) has emerged as a promising minimally invasive alternative to traditional therapies for primary aldosteronism (PA). However, incomplete ablation of aldosterone-producing adenomas (APA) tissue remains a key limitation. To address this challenge, we propose a novel hybrid approach integrating SAAE with selective adrenal venous embolization (SAVE), designed to optimize the therapeutic efficacy of APA. We report a 37-year-old man with confirmed unilateral PA. Left adrenal APA was diagnosed through computerized tomography and adrenal venous sampling. The patient underwent combined selective adrenal artery and venous embolization (SAAE-SAVE) for left-sided APA. Trans-catheter embolization of the dominant left adrenal artery and primary draining vein was performed using 2 ml anhydrous ethanol. This SAAE-SAVE protocol successfully normalized serum hypokalemia levels and achieved sustained blood pressure control at 1-month follow-up. SAAE-SAVE represents a transformative therapeutic alternative for APA treatment, and further research is needed to validate its safety and efficacy.